Synthesis of cationic dibenzosemibullvalene-based phase-transfer catalysts by di-π-methane rearrangements of pyrrolinium-annelated dibenzobarrelene derivatives - Heiko Ihmels; Jia Luo (Beilstein Journal of Organic Chemistry, 2011)
Dibenzobarrelene derivatives, that are annelated with a pyrrolinium unit [N,N-dialkyl-3,4-(9',10'-dihydro-9',10'-anthraceno-3-pyrrolinium) derivatives], undergo a photo-induced di-π-methane rearrangement upon triplet sensitization to give the corresponding cationic dibenzosemibullvalene derivatives [N,N-dialkyl-3,4-{8c,8e-(4b,8b-dihydrodibenzo[a,f]cyclopropa[cd]pentaleno)}pyrrolidinium derivatives]. Whereas the covalent attachment of a benzophenone functionality to the pyrrolinium nitrogen atom did not result in an internal triplet sensitization, the introduction of a benzophenone unit as part of the counter ion enables the di-π-methane rearrangement of the dibenzobarrelene derivative in the solid-state. Preliminary experiments indicate that a cationic pyrrolidinium-annelated dibenzosemibullvalene may act as phase-transfer catalyst in alkylation reactions.